Risk analysis of the MEG regeneration system in FPSO units: application of the Bowtie method - Olortiga Asencios , Yvan Jesus; da Silva Martins, Luiza Helena; Komesu, Andrea (Latin American Journal of Energy Research, 2025)
Oil and natural gas are the main energy sources used worldwide, playing a crucial role in transportation, electricity generation, and heating. Offshore production has expanded over the decades, driven by the search for new reserves and technological advancements. In this context, Floating Production Storage and Offloading (FPSO) platforms play a fundamental role, enabling the extraction, processing, and storage of oil and gas in remote offshore locations. One of the operational challenges in these units is the formation of hydrates, which can block production lines. To prevent this issue, Monoethylene Glycol (MEG) is used as an inhibitor, reducing hydrate formation and allowing for regeneration and reuse, making the process more efficient. The MEG regeneration system involves its separation from water and impurities in a distillation column, ensuring its reintegration into the production cycle. Offshore operations require stringent safety measures due to extreme environmental conditions and the presence of flammable substances. This study applied the Bowtie methodology to assess risks in the MEG regeneration module of an FPSO unit, identifying threats, preventive and mitigating barriers, and the consequences of system failures. The analysis revealed that failures in MEG regeneration can significantly impact platform operations, leading to environmental, economic, and safety risks. The integration of risk management strategies, combining the Bowtie method with other approaches such as HAZOP, enhances operational safety and improves the efficiency of offshore activities.